Cellular Immune Dysfunction in Obstructive Sleep Apnea - Ludwig, Katharina; Huppertz, Tilman; Radsak, Markus; Gouveris, Haralampos (Frontiers in Surgery, 2022)
Obstructive sleep apnea (OSA) is the most common sleep-related breathing disorder. Repetitive pauses in breathing during sleep cause a brief but recurrent decrease in oxygen saturation in organs and tissues (chronic intermittent tissue hypoxia). Many studies have proven a pro-inflammatory status in OSA patients. However, few reports are available on the effects of OSA on the cellular immune system, mostly focusing on single immune cell types and their subtypes. The aim of this Mini-Review is to summarize these reports, as OSA is associated with a high prevalence and comorbidities such as atherosclerosis, which are known to involve the cellular immune system.